2016
DOI: 10.15406/aovs.2016.04.00114
|View full text |Cite
|
Sign up to set email alerts
|

Three-Month Outcome of Ziv-Aflibercept for Diabetic Macular Edema

Abstract: Purpose: Is to show the 3-month efficacy and safety of treatment diabetic macular edema treated with intravitreal ziv-aflibercept as studies have shown that Ziv-aflibercept does not cause retinal pigment epithelial toxicity and to study it cost effectiveness.Methods: Ten eyes in eight patients diagnosed with central diabetic macular edema were enrolled for three consecutive intravitreal injection of ziv-aflibercept 1.25 mg every 4 weeks, a complete exam including BCVA and CRT at baseline and 12 weeks with eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Multiple studies have shown the safety and efficacy of intravitreal Ziv-aflibercept for the treatment of DME [ 3 , 20 , 21 ]. Moreover, in a double-blinded, three-arm, randomized clinical trial that compared 1.25 mg, 2.5 mg of Ziv-aflibercept and 1.25 mg of bevacizumab (Avastin; USA; Genentech/Roche) for the treatment of DME in 123 eyes and with a follow-up period of 12 weeks, there was no difference in visual outcomes between the two doses of Ziv-aflibercept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown the safety and efficacy of intravitreal Ziv-aflibercept for the treatment of DME [ 3 , 20 , 21 ]. Moreover, in a double-blinded, three-arm, randomized clinical trial that compared 1.25 mg, 2.5 mg of Ziv-aflibercept and 1.25 mg of bevacizumab (Avastin; USA; Genentech/Roche) for the treatment of DME in 123 eyes and with a follow-up period of 12 weeks, there was no difference in visual outcomes between the two doses of Ziv-aflibercept.…”
Section: Discussionmentioning
confidence: 99%
“…This adaptation of Ziv-Aflibercept, known as Zaltrap by Regeneron Pharmaceuticals, has undergone rigorous examination,demonstrating both its non-toxic nature and its effectiveness and safety in treating DME. [ 3 ]. Intravitreal steroids can be administered in two forms: as an intravitreal implant (dexamethasone or fluocinolone) or as a solution, such as triamcinolone, which is used for chronic or persistent cases.…”
Section: Introductionmentioning
confidence: 99%
“…Aflibercept has been approved by the USA FDA for ocular use whilst ziv-aflibercept was approved for the treatment of metastatic colorectal cancers and other cancers [7]. There had been earlier concerns about the intravitreal administration of ziv-aflibercept due to hyper-osmolality, but the potential retinal toxicity from its hyper-osmolality has been refuted by several studies [12, 15, 18, 2430]. Malik et al has shown that the use of 1.25mg and 2mg doses of ziv-aflibercept did not affect the viability of human retinal pigment epithelial cells in vitro although there was a mild reduction in mitochondrial membrane potential with the 2mg dose [31].…”
Section: Discussionmentioning
confidence: 99%
“…The first reported human use of intravitreal ziv-aflibercept resulted in successful treatment of a patient with refractory neovascular age-related macular degeneration (nAMD) (de Oliveira Dias et al 2015) and this was soon followed by a pilot study of four patients with nAMD and two patients with diabetic macular oedema (DME) (Mansour et al 2015). Based on the encouraging results of this pilot study, several prospective short-term and long-term studies (Figs 2-5) with monthly injections (de Andrade et al 2018), treat-and-extend (Mansour et al 2019a) or pro re nata (Eldeeb et al 2017;de Oliveira Dias et al 2019) regimens have been performed in the following countries: Brazil (Andrade et al 2016;de Oliveira Dias et al 2016;de Oliveira Dias et al 2019); Egypt (Ashraf et al 2017a); India (Videkar et al 2015;Chhablani et al 2016Chhablani et al , 2017Yogi et al 2017); Iran (Baghi et al 2017, Jabbarpoor Bonyadi et al 2018HodjatJalali et al 2017); Lebanon (Mansour et al 2015); Mexico (Hernandez-Da Mota et al 2019); Switzerland (Doepfner et al 2018), Syria (Marashi 2016); and the United States (Aleman et al 2019…”
Section: Early Clinical Usementioning
confidence: 95%